REPRESENTASI TUBUH PEREMPUAN PADA AKUN INSTAGRAM FOTOGRAFER @DARWISTRIADIGALLERY (ANALISIS SEMIOTIKA ROLAND BARTHES) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This study aims to understand the meaning of representation of women's bodies on the Instagram account of photographer @Darwisrtiadiartgallery with a study of Roland Barthes' semiotic analysis, using the media text analysis method with Roland Barthes' semiotic model technique. The data collection technique used is document analysis, obtained bycapturing 5 uploads contained in the feed @Darwistriadiartgallery Instagram.The results show that the denotative meaning that emerges from this stage of meaning is that female body features refer to the entire beauty of the body without using clothes that show some forms of body curves with style variants such as highlighting breasts, hips and culturally shaped feminine characteristics such as long hair, calves. slim, white skin, clean and smooth. Meanwhile, in connotation, the beauty of women is not only seen from the attractive and charming face, but the fragments of the female body which are shown as an ideal body shape also attract public attention and do not regard it as a form of pornography but as a work of art. Finally, the myth that arises from this research is to form a construction that requires that the female body displayed with lighting effects in the photo can eliminate the impression of vulgarity with the photographer's imagination which turns it into a work of art.The implication of this research is for further researchers to further deepen the scope of the representation of women's bodies. So that it is hoped that there will be other research as a comparison against the title of the same research on representation of the female body on the @Darwistriadiartgallery Instagram account by using different semiotic theories so that the knowledge obtained can be more diverse. Keyword: representation, women's bodies, Instagram